Prevalence and Diversity of Avian Haematozoan Parasites in Wetlands of Bangladesh. (21st January 2014) - Elahi, Rubayet; Islam, Ausraful; Hossain, Mohammad Sharif; Mohiuddin, Khaja; Mikolon, Andrea; Paul, Suman Kumer; Hosseini, Parviez Rana; Daszak, Peter; Alam, Mohammad Shafiul
Abstract : The parasites of genera Haemoproteus, Plasmodium, and Leucocytozoon are well-known avian haematozoa and can cause declined productivity and high mortality in wild birds. The objective of the study was to record the prevalence of haematozoan parasites in a wide range of wetland birds in Bangladesh. Six species of Haemoproteus, seven species of Plasmodium, one unidentified species of Leucocytozoon, and one unidentified microfilaria of the genus Paronchocerca were found. Data on the morphology, size, hosts, prevalence, and infection intensity of the parasites are provided. The overall prevalence among the birds was 29.5% (95 out of 322 birds). Of those, 13.2% (42 of 319) of birds were infected with Haemoproteus spp., 15.1% with Plasmodium spp. (48 of 319) and 0.6% with Leucocytozoon spp. (2 of 319). Two birds were positive for both Haemoproteus sp. and Plasmodium sp. A single resident bird, Ardeola grayii, was found positive for an unidentified microfilaria. Prevalence of infection varied significantly among different bird families. Wild birds of Bangladesh carry several types of haematozoan parasites. Further investigation with a larger sample size is necessary to estimate more accurately the prevalence of haematozoan parasites among wild birds as well as domestic ducks for better understanding of the disease ecology.